Concussion Symptom Underreporting Among Incoming National Collegiate Athletic Association Division I College Athletes. Issue 3 (May 2020) - Conway, Fiona N.; Domingues, Marianne; Monaco, Robert; Lesnewich, Laura M.; Ray, Anne E.; Alderman, Brandon L.; Todaro, Sabrina M.; Buckman, Jennifer F.
Abstract : Objective: Accurate diagnosis of sport-related concussions relies heavily on truthful self-reporting of symptom severity. Previous studies have emphasized lack of knowledge as a factor in symptom nondisclosure. This study sought to examine concussion knowledge and the relationship of knowledge to reasons for symptom nondisclosure. Design: Cross-sectional study. Setting: Data were collected during preparticipation athletic evaluations via electronic survey. Participants: One hundred fifty-six incoming National Collegiate Athletic Association Division I student-athletes. Main Outcome Measures: Survey items included previous concussion diagnosis, concussion fact and symptom knowledge, reasons and situational contexts for nondisclosure, and stakeholder attitudes. Results: Participants, on average, had substantial concussion symptom and fact knowledge. Unexpectedly, participants with higher concussion fact knowledge endorsed more reasons that athletes may hide symptoms. Concussion symptom knowledge was unrelated to reasons for nondisclosure. Athletes believed that symptom reporting was less likely in high-stakes versus low-stakes situations and consistently identified their teammates as holding attitudes that support underreporting and athletic trainers as engaging in behaviors that support player safety. Conclusions: Greater concussion knowledge did not reduce the number of reasons that participants viewed as drivers for concussion nondisclosure. In other words, participants understood why athletes choose to hide symptoms even when they also understood the symptoms, risks, sequelae, and consequences of concussion (and potential harm of nondisclosure). Situational contexts and important stakeholder attitudes also appeared to importantly influence symptom disclosure decisions. A multifaceted approach that goes beyond current educational strategies to addresses situational, social, and athletic pressures may be needed to initiate a widespread cultural shift away from concussion nondisclosure.